The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/crj.12965
|View full text |Cite
|
Sign up to set email alerts
|

Chest physiotherapy with early mobilization may improve extubation outcome in critically ill patients in the intensive care units

Abstract: Background: Extubation failure can lead to a longer intensive care unit (ICU) stay, higher mortality rate, and higher risk of requiring tracheostomy. Chest physiotherapy (CPT) can help patients in reducing the accumulation of airway secretion, preventing collapsed lung, improving lung compliance, and reducing comorbidities. Much research has investigated the correlation between CPT and respiratory system clearance. However, few studies have investigated the correlation between CPT and failed ventilator extubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 37 publications
0
25
1
1
Order By: Relevance
“…The management should not trigger severe cough and increase the work of breathing. High-frequency chest wall oscillation, [ 23 ] and oscillatory positive expiratory pressure (OPEP) are among the recommended treatment methods. [ 24 ]…”
Section: Respiratory Rehabilitation Treatment For Severely and Criticmentioning
confidence: 99%
“…The management should not trigger severe cough and increase the work of breathing. High-frequency chest wall oscillation, [ 23 ] and oscillatory positive expiratory pressure (OPEP) are among the recommended treatment methods. [ 24 ]…”
Section: Respiratory Rehabilitation Treatment For Severely and Criticmentioning
confidence: 99%
“…There was no significant difference in outcomes between HPRO and LPRO intake alone, but the significant difference in weaning and discharge status between UC versus MRP highlights what previous studies have shown regarding the benefits of exercise and physical rehabilitation in regard to functional outcomes in critical illness. 12,14,15 This study demonstrates that these interventions can be applied to survivors of critical illness requiring PMV with similar results in improved functional outcomes. One of the goals of adequate nutrition delivery, protein in particular, in critically ill patients is to attenuate acute skeletal muscle wasting, which is a significant contributor to ICU-acquired weakness.…”
Section: Discussionmentioning
confidence: 59%
“…Recent studies have confirmed that CPT in critically ill patients is able to improve respiratory function immediately after extubation ( Papadopoulos and Kyprianou, 2002 ; Wang et al, 2018 ). As suggested by the ARIR position paper ( Lazzeri et al, 2020 ), CPT may be considered in all COVID-19 patients who require mechanical ventilation, as well as during and after the extubation process.…”
Section: Chest Physiotherapy For Mechanically Ventilated Covid-19 Patmentioning
confidence: 90%